Reaction Kinetics Analysis of Treatment Process on Light-Induced Degradation for p-Type Passivated Emitter and Rear Contact Solar Cell Module with Gallium Cz-Si Wafer - Min-Gwang Seok; Yangdo Kim; Soo Min Kim (Energies, 2022)
The light-induced degradation (LID) phenomenon in solar cells reduces power generation output. Previously, a method was developed to prevent LID where a group III impurity that can replace boron is added to the silicon wafer. However, in a subsequent study, performance degradation was observed in gallium-doped solar wafers and cells, and a degradation pattern similar to that occurring in light and elevated temperature-induced degradation (LeTID) was reported. In this study, a 72-cell module was fabricated using gallium-doped PERC cells, and the treatment of the LID process for carrier injection in the range of 1 to 7 A at 130 °C was analyzed using kinetic theory. We selectively heated only the solar cells inside a 72-cell module using a half-bridge resonance circuit for remote heating. To monitor the treatment of LID process in real time, a custom multimeter manufactured using an ACS758 current sensor and a microcomputer was used. Least-squares curve fitting was performed on the measured data using a reaction kinetics model. When the carrier-injection condition was applied to the gallium-doped PERC solar cell module at a temperature of 130 °C, the observed degradation and treatment pattern were similar to LeTID. We assumed that the treatment rate would increase as the size of the injected carrier increased; however, the 5 A condition exhibited the fastest treatment rate. It was deduced that the major factors of change in the overall treatment of the LID process vary depending on the rate of conversion from the LID state to the treatment state. In conclusion, it can be expected that the deterioration state of the gallium-doped solar cell module changes due to the treatment rate that varies depending on the carrier-injection conditions.